Acceptance of student of Malacca city campus and public around Kampung Morten about traditional games / Mohammad Sahnizam Ahmat - Ahmat, Mohammad Sahnizam (2014)
The existence of a nation is determined by the character possessed. However, the question of national character is the issues raised in today's society. The question is can be the perfect solution to this problem is to build and develop our country's nature and character of its own. One of them is the ideal medium for developing and expanding human nature is through education. In the course of the learning process within the scope of education is certainly supported by the Medium of learning. Looking at the fact that the lack of effective instructional media used, it will require a change and innovation. Therefore, the media should also be adapted to learning the identity and culture of the country. The learning process is based on the character of education, one that can be supported by traditional game to produce a vehicle for educational fun. The data used in this paper come from a variety of speaker's literature and support related issues. In writing this paper using the methods of research and literature related to the research and analysis to support the discussion. Followed by the synthesis process by linking formulation of the problem, purpose of writing, and discussion conducted by systematic logical. Next is drawn a general nature and some recommendations for further action. It was found that the potential of traditional games in imparting education pillars of the nation's character can be evidenced by the many linkages between the traditional games with character education of the nation. Along with the implementation of traditional game activities can be done in order to establish the character of the younger generation, among others through the family environment (informal), school environment(formal), and society (non-formal)